3.0k views
5 votes
Add, subtract and multiply p(x)=x^3-3x-1 q(x)=x-1

User Hmjd
by
5.2k points

1 Answer

1 vote

Answer:

## Addition: P(x) + Q(x)

P(x)+Q(x) = X³ - 3X - 1 + X - 1

=X³ - 2X - 2

So P(x) + Q(x) = X³ - 2X - 2

## Subtraction: P(x) - Q(x)

P(x) - Q(x) = X³ - 3X - 1 - (X - 1)

= X³ - 3X - 1 - X + 1

= X³ - 4X

So P(x) - Q(x) = X³ - 4X

## Multiplication: P(x) × Q(x)

P(x) × Q(x) = (X³ - 3X - 1) × (X - 1)

= X⁴ - X³ - 3X² + 3X - X + 1

= X⁴ -X³ - 3X² + 2X + 1

So P(x) × Q(x) = X⁴ -X³ - 3X² + 2X + 1

User Julien Hoarau
by
4.9k points